2018
DOI: 10.30773/pi.2018.09.28
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Online Imagery-Based Treatment Program in Patients with Workplace-Related Posttraumatic Stress Disorder: A Pilot Study

Abstract: ObjectiveWe developed easily accessible imagery-based treatment program for patients with post-traumatic stress disorder (PTSD) related to workplace accidents and investigated the effects of the program on various PTSD related symptoms. MethodsThe program was based on an online platform and consisted of eight 15-min sessions that included script-guided imagery and supportive music. Thirty-five patients with workplace-related PTSD participated in this program 4 days per week for 4 weeks. Its effects were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The MBI which used in this study is the combination of moving meditation (i.e., Brain Wave Vibration meditation) and focused attention meditation (i.e., Sangdahnjeon meditation). According to previous investigations, Brain Wave Vibration meditation significantly reduces depression, anxiety, stress, [ 26 , 48 50 ] improves EI, [ 48 , 51 ] and global sleep quality. [ 24 ] In the current study, the self-report questionnaires exhibited consistent results with the previous reports of the brain wave vibration meditation: depression, anxiety, stress, EI, and sleep quality exhibited improvements with a significant difference or a tendency of significance in the experimental group compared to the control group (Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The MBI which used in this study is the combination of moving meditation (i.e., Brain Wave Vibration meditation) and focused attention meditation (i.e., Sangdahnjeon meditation). According to previous investigations, Brain Wave Vibration meditation significantly reduces depression, anxiety, stress, [ 26 , 48 50 ] improves EI, [ 48 , 51 ] and global sleep quality. [ 24 ] In the current study, the self-report questionnaires exhibited consistent results with the previous reports of the brain wave vibration meditation: depression, anxiety, stress, EI, and sleep quality exhibited improvements with a significant difference or a tendency of significance in the experimental group compared to the control group (Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Brain education meditation (BEM) (also referred as brain wave vibration meditation) is a modernized mind-body training method which is rooted in Korean Sundo tradition and consists of several techniques including exercises which improves the connection between the brain and body, such as qigong, breathing postures, body awareness meditation, and brain wave vibration meditation with rhythmic body movement [ 22 – 28 ], and has been investigated for its differences from other mind-body interventions such as mindfulness meditation and yoga [ 23 , 26 ]. BEM is associated with its effects on various body systems such as changes in brain structure and function [ 24 , 29 31 ], improvements in emotion and cognition [ 32 34 ], and suppression of inflammation [ 25 , 35 ]. Brain education healing point (BHP) meditation, which is used in the current study, is a meditation program that combines acupressure-like stimulation with the meditation of the abovementioned BEM tradition [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Over the past decade, music therapy has emerged as an alternative and less linguistically intensive treatment modality for individuals suffering from PTSD. Empirical research has demonstrated its promising efficacy and favourable feasibility in alleviating PTSD symptoms as well as comorbid depressive, anxiety, and insomnia symptoms in individuals with PTSD (Blanaru et al, 2012 ; Hirschberg et al, 2020 ; Landis-Shack et al, 2017 ; Lee et al, 2018 ; Macfarlane et al, 2019 ; Ophir & Jacoby, 2020 ). Nevertheless, it is worth noting that the majority of existing studies exploring the efficacy of music therapy primarily consist of single-arm clinical trials or qualitative studies.…”
Section: Introductionmentioning
confidence: 99%